Organizational citizenship behavior levels of nurses and effective factors - Serap Altuntaş; Ülkü Baykal (Association of Nurse Managers, 2014)
OBJECTIVE: INTRODUCTION: Nurses who are the most active members of health staff should display high level of organizational citizenship behavior in order to more efficiently provide health services. Certain factors like nurse and patient satisfaction, motivation and performances of nurses promote organizational commitment. Nurses' job satisfaction and commitment to institution reduce the rate of job quitting. AIM: This descriptive and comparative study was carried out to determine organizational citizenship behavior levels of nurses and effective factors. METHODS: METHODS: Study population includes nurses employed in 11 hospitals with ≥100 bed capacity and located in European Side of Istanbul and not specialized only in a specific area. Personal Information Form and the Organizational Citizenship Level Scale were used for data collection. Ethical committee consent, approvals of related organizations and participant consent were obtained. Study data was analyzed by frequency and percentage distributions, ANOVA, Kruskal Wallis, Tukey HSD and t-test with SPSS 11.5 packet software. RESULTS: RESULTS: Nurses were found to display high levels of organizational citizenship behavior. The factors including organizations, age, position, organizational experience, intentional choice of profession, shift, working type, job satisfaction, and intention to leave from organization were found to be effective on certain organizational citizenship behaviors of nurses. CONCLUSION: CONCLUSION: Study results indicated that organizational citizenship behavior levels of nurses were affected by certain factors.